Should smart investors buy funds with high returns in the past? - Frederic Palomino; Harald Uhlig (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Newspapers and weekly magazines catering to the investing crowd often rank funds according to the returns generated in the past. Aside from satisfying sheer curiosity, these numbers are probably also the basis on which investors pick a fund to invest in. In this article, we fully characterize the equilibrium in a game between a mutual fund manager of unknown ability who controls the riskiness of his portfolio and investors who only observe realized returns. We derive conditions under which (i) investors invest in the fund if the realized return falls within some interval, i.e., is neither too low nor too high, (ii) an informed fund manager picks a portfolio of minimal riskiness and (iii) an uninformed mutual fund manager will pick a portfolio with higher risk, gambling on a lucky outcome, (iv), when the fee structure is endogenous, both types of manager choose the same fraction-of-fund fee structure. Our results are consistent with empirical evidence about the lack of persistence of top performance, and about the very wide use of fraction-of-fund fee structure among mutual funds.
urn:nbn:de:kobv:11-10048867
Keywords: 330